Analisis Trend Produksi Padi Sawah Daerah Sentra Sipilu (Sidrap, Pinrang, Luwu) Terhadap Produksi Padi Sawah di Sulawesi Selatan - Kartia Kartia; Arifin Arifin; Mohammad Anwar Sadat (Universitas Muslim Maros, 2021)
This research was conducted in Sidrap Regency. Pinrang, Luwu in South Sulawesi. This location was chosen with the consideration that it has been managing the Paddy Field for a long time. The data used is secondary data, namely data obtained from agencies / institutions related to or related to this research. The purpose of this study was to determine the production of lowland rice in the Sentra Sipilu area (Sidrap, Pinrang, Luwu) on lowland rice production in South Sulawesi. The collected data is then tabulated to obtain the real data used for analysis purposes. This study used a quantitative descriptive analysis method to determine the amount of income obtained by farmers from lowland rice production in the Sipilu center area on lowland rice production in South Sulawesi. The results showed that the amount of income obtained by farmers from lowland rice production in the central area of ​​Sipilu was 14,136,031.31 to rice production in South Sulawesi as much as 55,045,131. the results of the calculation have been able to produce lowland rice production at the Sipilu center in South Sulawesi.